Business Plan : Yummy Crepe Enterprise / Wan Muhammad Irfan Wan Nazli … [et al.] - Wan Nazli, Wan Muhammad Irfan; Mohd Azman, Muhammad Azrel Amer; Mohd Zukifli, Ahmad Idham Hakimi; Abdullah, Muhammad Alif Aqasyah; Mohd Asmawi, Muhammad Haikal (2021)
Yummy Crepe Enterprise using a fresh ingredient to bake a delicious crepe for customer to taste with their love ones and we also provide top service to our customer. We hope to impress their expectation with our own recipes. We will continue to provide a good service and produce high-quality crepe for our consumer to satisfy their expectation. In conclusion, we hope that our business will continue to grow and be able to bring joy to others that bought our crepe and fill their hungry stomach.